ISLAM DAN WELFARE STATE (Sebuah Analisis Perbandingan) - muhaimin, muhaimin (Islamic Economics and Business Faculty of UIN Antasari, 2015)
Abstract: Islamic concept is fundamentally different from the welfare state, the Islamic system aims tomaterial and spiritual well-being as well. while the concept of the welfare state is limited to achieving thegoal of material. This paper discusses the concept of the welfare state as a tempting offer for socialwelfare and how Muslims react. Conclusions concept of the welfare state, many experienced failuresand facing crises, a data indicate that many classical economic problems, such as poverty, unequal distri-bution of income, fiscal deficit, unemployment, and others. While the concept of Islam that empha-sizes the moral consciousness of wealth for the society.